2017
DOI: 10.1002/ijgo.12371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Copenhagen Index versus ROMA for the preoperative assessment of women with ovarian tumors

Abstract: CPH-I is a potential tumor index that is independent of menopausal status. It might be applied as a simple alternative to ROMA in settings of basic medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 29 publications
7
47
2
2
Order By: Relevance
“…With regard to the diagnostic value of the four indices, we found that the AUC-ROC of HE4, ROMA, and CPH-I were bigger than that of CA125 (0.807, 0.807, and 0.810 vs. 0.694, P < 0.001). However, our AUC of ROMA and CPH-I were much higher than that reported in Minar et al's study (0.65 and 0.67, respectively) when distinguishing 42 BOT I+II patients from 33 EOC I+II patients [15]. The difference maybe mainly due to different races which may cause different proportions of pathological subtypes in ovarian tumors [2729], further resulting in different ROMA and CPH-I [20, 21].…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…With regard to the diagnostic value of the four indices, we found that the AUC-ROC of HE4, ROMA, and CPH-I were bigger than that of CA125 (0.807, 0.807, and 0.810 vs. 0.694, P < 0.001). However, our AUC of ROMA and CPH-I were much higher than that reported in Minar et al's study (0.65 and 0.67, respectively) when distinguishing 42 BOT I+II patients from 33 EOC I+II patients [15]. The difference maybe mainly due to different races which may cause different proportions of pathological subtypes in ovarian tumors [2729], further resulting in different ROMA and CPH-I [20, 21].…”
Section: Discussioncontrasting
confidence: 65%
“…Studies showed that levels of HE4 and CA125 and the ROMA index were all higher in EOC I-IV than that of BOT I-IV [16, 20, 24, 25], with other two studies reporting the same trend for CPH-I [15, 19]. Moreover, Kotowicz et al showed that levels of HE4 and CA125 and the ROMA index were all higher in EOC I+II than BOT I-IV [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations